Evaluation method of all-solid-state lithium ion battery
By comparing the X-ray diffraction pattern after mixing the oxide-based solid electrolyte with the positive electrode active material and firing, it is determined whether reactants have been generated, and the problem of difficult to efficiently evaluate the battery characteristics of oxide-based all-solid lithium-ion batteries in the prior art is solved, and efficient evaluation of battery characteristics is achieved.
Patent Information
- Application Number
- CN202380059107.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-02-28
- Publication Date
- 2025-03-25
AI Technical Summary
The prior art is difficult to efficiently evaluate the battery characteristics of oxide-based all-solid lithium-ion batteries.
By comparing the X-ray diffraction pattern of the pressed powder obtained by mixing the oxide-based solid electrolyte with the positive electrode active material and pressing it with the X-ray diffraction pattern of the sintered body obtained after firing, it was determined whether the reactants were generated, and the battery characteristics were evaluated.
It has achieved efficient evaluation of the battery characteristics of an oxide-based all-solid lithium-ion battery, and can judge the reactivity of the positive electrode active substance and the solid electrolyte, ensuring good battery characteristics.
Smart Images

Figure CN119698715A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an evaluation method for an all-solid-state lithium-ion battery. Background Art
[0002] In recent years, with the rapid popularization of information-related equipment, communication equipment, etc. such as personal computers, cameras and portable phones, the development of batteries used as their power sources has received attention. Among these batteries, lithium-ion batteries have received attention from the perspective of high energy density. In addition, for lithium secondary batteries used in large-scale applications such as power sources for vehicle-mounted use and load leveling, it is also required to improve energy density and battery characteristics.
[0003] Lisicon oxide-based solid electrolytes are solid materials that conduct Li ions and are expected to be solid electrolytes for next-generation all-solid-state batteries. In addition, they have the following advantages: they can introduce Li deficiency and excess Li by replacing ions with different valence numbers, and can produce materials combined with various elements.
[0004] Non-patent document 1 discloses that Li 3.5 Ge 0.5 V 0.5 O4 is combined with NCM111 (a positive electrode active material containing Ni, Co and Mn in a composition ratio of 1:1:1) as a Ni-Co-Mn ternary positive electrode active material to produce a battery cell that is co-sintered by discharge plasma sintering. As a result, a sintered body for a battery cell that exhibits stable charge and discharge behavior can be produced.
[0005] Prior art literature
[0006] Non-patent literature
[0007] Non-patent literature 1: Toyoki Okumura, Tomonari Takeuchi, and Hironori Kobayashi, All-Solid-State Batteries with LiCoO2-Type Electrodes: Realization of anImpurity-Free Interface by Utilizing a CosinterableLi3.5Ge0.5V0.5O4Electrolyte, ACS Appl. Energy Mater. (2021), 4, 1, 30-34. Summary of the invention
[0008] Problems to be solved by the invention
[0009] Oxide-based all-solid-state lithium-ion batteries using non-flammable oxide-based solid electrolytes have attracted attention as next-generation batteries that are significantly safer and more reliable than conventional lithium-ion batteries.
[0010] The battery characteristics of oxide-based all-solid-state batteries have been evaluated from various viewpoints in the past, but there is still room for development of a method for more efficiently evaluating the battery characteristics of oxide-based all-solid-state batteries.
[0011] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a method for efficiently evaluating battery characteristics of an oxide-based all-solid-state battery.
[0012] Solutions for solving problems
[0013] The present invention completed based on the above findings is defined by the following (1) to (3).
[0014] (1) A method for evaluating an all-solid-state lithium-ion battery, wherein the all-solid-state lithium-ion battery comprises: a solid electrolyte layer containing an oxide-based solid electrolyte, a positive electrode layer containing a positive electrode active material, and a negative electrode layer. In the method for evaluating the all-solid-state lithium-ion battery, an X-ray diffraction pattern of a powder compact obtained by mixing and pressing the oxide-based solid electrolyte and the positive electrode active material is compared with an X-ray diffraction pattern of a sintered body obtained by sintering the powder compact, thereby evaluating the battery characteristics of the all-solid-state lithium-ion battery.
[0015] (2) An evaluation method for an all-solid-state lithium-ion battery according to (1), wherein an X-ray diffraction pattern of a powder compact obtained by mixing and pressing the oxide-based solid electrolyte and the positive electrode active material is compared with an X-ray diffraction pattern of a sintered body obtained by sintering the powder compact; when the X-ray diffraction patterns are different, it is judged that a reaction product of the oxide-based solid electrolyte and the positive electrode active material is generated; and when the X-ray diffraction patterns are the same, it is judged that a reaction product of the oxide-based solid electrolyte and the positive electrode active material is not generated, thereby evaluating the battery characteristics of the all-solid-state lithium-ion battery.
[0016] (3) The method for evaluating an all-solid-state lithium-ion battery according to (1) or (2), wherein the oxide-based solid electrolyte has a composition formula 1: Li α A x M y O4 (in the composition formula 1, A is Ge, Si or Ti, M is V, P or As, 3.25≤α≤3.75, 0.30≤x≤0.75, and 0.25≤y≤0.70), the positive electrode active material is represented by the composition formula 2: Lia Ni b Co c Mn d O2 (in composition formula 2, 1.00≤a≤1.08, 0.60≤b≤0.90, and b+c+d=1.0) is represented.
[0017] Effects of the Invention
[0018] According to the present invention, a method for efficiently evaluating the battery characteristics of an oxide-based all-solid-state battery can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Schematic diagram of an all-solid-state lithium-ion battery according to an embodiment of the present invention.
[0020] Figure 2 This is the X-ray diffraction pattern of Example 1.
[0021] Figure 3 This is the X-ray diffraction pattern of Example 2.
[0022] Figure 4 This is the X-ray diffraction pattern of Example 3.
[0023] Figure 5 This is the X-ray diffraction pattern of Example 4.
[0024] Figure 6 This is the X-ray diffraction pattern of Example 5.
[0025] Figure 7 This is the X-ray diffraction pattern of Example 6.
[0026] Figure 8 This is the X-ray diffraction pattern of Example 7.
[0027] Fig. 9 This is the X-ray diffraction pattern of Example 8.
[0028] Fig.10 This is the X-ray diffraction pattern of Example 9.
[0029] Fig.11 This is the X-ray diffraction pattern of Comparative Example 1.
[0030] Fig.12 This is the X-ray diffraction pattern of Comparative Example 2.
[0031] Fig.13 This is the X-ray diffraction pattern of Comparative Example 3. DETAILED DESCRIPTION
[0032] Next, specific embodiments of the present invention will be described in detail with reference to the accompanying drawings. The present invention is not limited to the following embodiments, and it should be understood that appropriate design changes and improvements can be made based on common sense of those skilled in the art without departing from the scope of the present invention.
[0033] <Evaluation method of all-solid-state lithium-ion batteries>
[0034] With regard to the evaluation method of an all-solid-state lithium-ion battery according to an embodiment of the present invention, wherein the all-solid-state lithium-ion battery comprises: a solid electrolyte layer comprising an oxide-based solid electrolyte, a positive electrode layer comprising a positive electrode active material, and a negative electrode layer, in the evaluation method of the all-solid-state lithium-ion battery, an X-ray diffraction pattern of a powder compact obtained by mixing and pressing the oxide-based solid electrolyte and the positive electrode active material is compared with an X-ray diffraction pattern of a sintered body obtained by sintering the powder compact, thereby evaluating the battery characteristics of the all-solid-state lithium-ion battery.
[0035] As a specific example of the evaluation method of the all-solid-state lithium-ion battery as an embodiment of the present invention, first, the positive electrode active material and the oxide-based solid electrolyte are weighed in a manner to form a specified mass ratio, and gently mixed manually with a pestle and mortar to obtain a positive electrode material / solid electrolyte mixed powder. Then, the obtained mixed powder is pressed and molded, for example, at 300 to 400 MPa to make a mixed powder compact. Then, the obtained compact is placed in an alumina boat covered with gold foil, for example, after calcining at 700 to 900°C for 1 to 3 hours, the obtained calcined body is crushed with a pestle and mortar. The mixed calcined powder obtained in this way is subjected to the reactivity evaluation (XRD evaluation) shown below.
[0036] That is, the reactivity of the positive electrode active material and the solid electrolyte of the all-solid-state lithium-ion battery is analyzed by powder X-ray diffraction method: XRD (θ / 2θ method) according to the following conditions. When the X-ray diffraction pattern obtained by the positive electrode material / solid electrolyte mixed powder is different before and after firing, it means that a new peak is generated after firing and the peak existing before firing disappears, so the reactant of the positive electrode active material and the oxide-based solid electrolyte (NCM) can be evaluated as "present". On the other hand, when the obtained X-ray diffraction patterns are the same, the reactant of the positive electrode active material and the oxide-based solid electrolyte (NCM) can be evaluated as "absent".
[0037] ·X-ray diffraction apparatus: SmartLab manufactured by Rigaku Corporation.
[0038] ·Light source: CuKα rays.
[0039] Voltage: 40kV.
[0040] Current: 30mA.
[0041] In this way, the reactivity of the positive electrode active material and the oxide-based solid electrolyte (NCM) can be evaluated, and the case where the above-mentioned reactant is evaluated as "none" can be evaluated as the battery characteristics of the all-solid-state lithium-ion battery are good. Therefore, the battery characteristics of the all-solid-state lithium-ion battery can be efficiently evaluated.
[0042] <All-solid-state lithium-ion battery>
[0043] The all-solid-state lithium-ion battery to be evaluated in the evaluation method of the all-solid-state lithium-ion battery according to the embodiment of the present invention includes: a solid electrolyte layer including an oxide-based solid electrolyte, a positive electrode layer including a positive electrode active material, and a negative electrode layer. The all-solid-state lithium-ion battery can be used Figure 1 The composition shown.
[0044] (Solid electrolyte layer)
[0045] The composition of the solid electrolyte layer of the present embodiment is not particularly limited, and for example comprises a composition formula 1: Li α A x M y O4 (in composition formula 1, A is Ge, Si or Ti, M is V, P or As, 3.25≤α≤3.75, 0.30≤x≤0.75, and 0.25≤y≤0.70) is an oxide-based solid electrolyte. The oxide-based solid electrolyte of this embodiment has Li as a LISICON-type solid electrolyte. α Ge x V y O4 parent material, or a composition formed by replacing Si, Ti, P or As in the parent material. According to such a composition, the types of elements constituting the oxide-based solid electrolyte increase, the activation energy decreases, and thus an oxide-based solid electrolyte with good ion conductivity can be obtained. As a result, the capacity of the all-solid-state lithium-ion battery becomes larger.
[0046] It should be noted that, in the present invention, the oxide-based solid electrolyte refers to a solid electrolyte having an oxygen-containing acid ion in the framework thereof, in which an oxygen atom is coordinately bonded to a central element, as a counter anion for a lithium ion.
[0047] In the case of the oxide-based solid electrolyte of the present embodiment, in the above composition formula 1, if α is less than 3.25, the problem of reduced ion conductivity due to low carrier concentration may occur. In addition, if α is greater than 3.75, the problem of difficulty in single-phase synthesis may occur. In the case of the oxide-based solid electrolyte of the present embodiment, in the above composition formula 1, preferably 3.4≤α≤3.7.
[0048] In the oxide-based solid electrolyte of the present embodiment, in the above composition formula 1, if x is less than 0.30, a Li4GeO4 phase with low ion conductivity may be generated. In addition, if x is greater than 0.75, the distance between Li sites becomes longer due to the increase in the lattice, and the ion conductivity may decrease. In the oxide-based solid electrolyte of the present embodiment, in the above composition formula 1, preferably 0.4≤x≤0.6.
[0049] In the case of the oxide-based solid electrolyte of the present embodiment, in the above composition formula 1, if y is less than 0.25, the effect of reducing the activation energy due to element substitution is weak, so the effect of improving the ionic conductivity may be small. In addition, if y is greater than 0.70, impurity phases such as Li4VO4 may be generated, and the ionic conductivity may be reduced. In the case of the oxide-based solid electrolyte of the present embodiment, in the above composition formula 1, preferably 0.3≤y≤0.6.
[0050] The average particle size of the oxide-based solid electrolyte of the present embodiment is not particularly limited, and may be 0.01 to 100 μm, 0.1 to 100 μm, or 0.1 to 50 μm.
[0051] The oxide-based solid electrolyte of the present embodiment can be produced as follows.
[0052] First, raw materials are weighed in a glove box with an inert gas atmosphere such as argon or nitrogen to obtain a predetermined composition. Examples of the raw materials used here include LiOH·H2O, GeO2, V2O5, SiO2, TiO2, H3PO4, and H3AsO3.
[0053] Next, the mixture is mixed for 5 to 30 minutes using a mortar or the like to prepare a mixed powder. At this time, it is preferred that the mixed powder be mixed for a period of time sufficient to achieve an average particle size of 5 to 40 μm.
[0054] Next, the mixed powder is placed in an alumina sagger and sintered at 600 to 1000° C. for 1 to 20 hours to produce a composite material having a composition formula 1: Li α A x M y The oxide-based solid electrolyte of this embodiment is represented by O4 (in composition formula 1, A is Ge, Si or Ti, M is V, P or As, 3.25≤α≤3.75, 0.30≤x≤0.75, and 0.25≤y≤0.70).
[0055] The average thickness of the solid electrolyte layer of the lithium ion battery formed of the oxide-based solid electrolyte of this embodiment is not particularly limited and can be appropriately designed according to the purpose. The average thickness of the solid electrolyte layer of this embodiment can be, for example, 50 μm to 500 μm, or 50 μm to 100 μm.
[0056] The method for forming the solid electrolyte layer of the present embodiment is not particularly limited and can be appropriately selected according to the purpose. Examples of the method for forming the solid electrolyte layer of the present embodiment include sputtering using a solid electrolyte target or compression molding of a solid electrolyte.
[0057] (Positive electrode layer)
[0058] The composition of the positive electrode active material contained in the positive electrode layer of this embodiment is not particularly limited, and is, for example, represented by the composition formula 2: Li a Ni b Co c Mn d O2 (in composition formula 2, 1.00≤a≤1.08, 0.60≤b≤0.90, and b+c+d=1.0). More specifically, the positive electrode layer of the present embodiment can be formed into a layered positive electrode layer using a positive electrode composite material formed by mixing the positive electrode active material represented by the above composition formula 2 with the oxide-based solid electrolyte of the present embodiment. The content of the positive electrode active material in the positive electrode layer is, for example, preferably 50 mass % or more and 99 mass % or less, and more preferably 60 mass % or more and 90 mass % or less.
[0059] The positive electrode active material of the present embodiment is a high-nickel NCM positive electrode active material with a Ni ratio as high as 0.60 to 0.90 as shown in the above composition formula 2. When such a high-nickel positive electrode active material is used, the capacity of the all-solid-state lithium ion battery is generally increased. In addition, from such a viewpoint, in the above composition formula 2, 0.80≤b≤0.90 is more preferably used. The positive electrode active material of the present embodiment is not particularly limited as long as it satisfies the above composition formula 2, and a known positive electrode active material can be used.
[0060] High nickel NCM positive electrode active materials with a high Ni ratio of 0.60 to 0.90 have the following problem in the past: they react with solid electrolytes to generate reactants that do not conduct Li ions and cannot work as batteries, but such high nickel NCM positive electrode active materials do not generate reactants with the oxide-based solid electrolyte shown in the above composition formula 1. Therefore, according to the following all-solid-state lithium-ion battery, an oxide-based all-solid-state battery with high capacity can be obtained, wherein the all-solid-state lithium-ion battery has an oxide-based solid electrolyte shown in the above composition formula 1 in the solid electrolyte layer and a high nickel NCM positive electrode active material shown in the above composition formula 2 in the positive electrode layer.
[0061] The positive electrode composite material may further include a conductive aid. As the conductive aid, a carbon material, a metal material or a mixture thereof may be used. The conductive aid may, for example, also include at least one element selected from the group consisting of carbon, nickel, copper, aluminum, indium, silver, cobalt, magnesium, lithium, chromium, gold, ruthenium, platinum, beryllium, iridium, molybdenum, niobium, osmium, rhodium, tungsten and zinc. The conductive aid is preferably a carbon single substance with high conductivity; a metal single substance, mixture or compound containing carbon, nickel, copper, silver, cobalt, magnesium, lithium, ruthenium, gold, platinum, niobium, osmium or rhodium. As a carbon material, for example, carbon black such as Ketjen black, acetylene black, DENKABLACK, thermal black, channel black, graphite, carbon fiber, activated carbon, etc. can be used.
[0062] The average thickness of the positive electrode layer of the all-solid-state lithium ion battery is not particularly limited and can be appropriately designed according to the purpose. The average thickness of the positive electrode layer of the all-solid-state lithium ion battery can be, for example, 1 μm to 100 μm, or 1 μm to 10 μm.
[0063] There is no particular limitation on the method for forming the positive electrode layer of the all-solid-state lithium ion battery, and it can be appropriately selected according to the purpose. As the method for forming the positive electrode layer of the all-solid-state lithium ion battery, for example, a method of compression molding the positive electrode active material for the all-solid-state lithium ion battery can be cited.
[0064] (Negative electrode layer)
[0065] The negative electrode layer of the all-solid-state lithium ion battery is not particularly limited, and may be a layered negative electrode layer formed by a known all-solid-state lithium ion battery negative electrode active material. In addition, the negative electrode layer may also be a layered negative electrode layer formed by mixing a known all-solid-state lithium ion battery negative electrode active material with a solid electrolyte. The content of the negative electrode active material in the negative electrode layer is, for example, preferably 10% by mass or more and 99% by mass or less, more preferably 20% by mass or more and 90% by mass or less.
[0066] The negative electrode layer, like the positive electrode layer, may also contain a conductive aid. The conductive aid may be the same material as that described in the positive electrode layer. As the negative electrode active material, for example, a carbon material may be used, specifically, artificial graphite, graphite carbon fiber, resin-sintered carbon, pyrolysis vapor-grown carbon, coke, mesocarbon micro-beads (MCMB: mesocarbon micro-beads), furfuryl alcohol resin-sintered carbon, polyphenylene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, and difficult-graphitizable carbon, or a mixture thereof. In addition, as the negative electrode material, for example, metals such as lithium metal, indium metal, aluminum metal, and silicon metal themselves, or alloys formed by combining with other elements or compounds may be used.
[0067] The average thickness of the negative electrode layer of the all-solid-state lithium ion battery is not particularly limited and can be appropriately selected according to the purpose. The average thickness of the negative electrode layer of the all-solid-state lithium ion battery can be, for example, 1 μm to 100 μm, or 1 μm to 10 μm.
[0068] There is no particular limitation on the method for forming the negative electrode layer of the all-solid-state lithium-ion battery, and it can be appropriately selected according to the purpose. As the method for forming the negative electrode layer of the all-solid-state lithium-ion battery, for example, there can be listed: a method of compression molding the negative electrode active material particles, a method of vapor deposition of the negative electrode active material, etc.
[0069] Other members constituting the lithium ion battery are not particularly limited and may be appropriately selected depending on the intended purpose. Examples thereof include a positive electrode current collector, a negative electrode current collector, and a battery case.
[0070] The size and structure of the positive electrode current collector are not particularly limited and may be appropriately selected depending on the intended purpose.
[0071] Examples of the material of the positive electrode current collector include die steel, stainless steel, aluminum, aluminum alloy, titanium alloy, copper, gold, and nickel.
[0072] Examples of the shape of the positive electrode current collector include a foil shape, a plate shape, and a mesh shape.
[0073] The average thickness of the positive electrode current collector may be, for example, 10 μm to 500 μm, or 50 μm to 100 μm.
[0074] The size and structure of the negative electrode current collector are not particularly limited and may be appropriately selected depending on the intended purpose.
[0075] Examples of the material of the negative electrode current collector include die steel, gold, indium, nickel, copper, and stainless steel.
[0076] Examples of the shape of the negative electrode current collector include a foil shape, a plate shape, and a mesh shape.
[0077] The average thickness of the negative electrode current collector may be, for example, 10 μm to 500 μm, or 50 μm to 100 μm.
[0078] There is no particular limitation on the battery case, and it can be appropriately selected according to the purpose, and for example, known laminated films that can be used in existing all-solid-state batteries can be listed. As laminated films, for example, laminated films made of resin, films formed by vapor deposition of metal on laminated films made of resin, etc. can be listed.
[0079] The shape of the battery is not particularly limited and may be appropriately selected depending on the intended purpose. Examples thereof include cylindrical, rectangular, button, coin, and flat shapes.
[0080] Example
[0081] Hereinafter, examples are provided for better understanding of the present invention and its advantages, but the present invention is not limited to these examples.
[0082] <1. Preparation of oxide-based solid electrolyte>
[0083] (Examples 1 to 4)
[0084] In a glove box with an argon atmosphere, the raw materials were weighed in such a way that the raw material charge composition became the stoichiometric composition of the target compound, and mixed in a mortar for 15 minutes to prepare a mixed powder. Next, about 2 g of the mixed powder was placed in an alumina boat, pre-calcined at 600°C for 12 hours, and manually crushed in a mortar to obtain a pre-calcined powder. Then, about 1 g of the pre-calcined powder was placed in an alumina boat again, and formally calcined at 700°C for 12 hours, thereby obtaining a Li 3.5 Ge 0.5 V 0.5 An oxide-based solid electrolyte with a composition of O4.
[0085] (Example 5)
[0086] In a glove box with an argon atmosphere, the raw materials were weighed so that the raw material charge composition became the stoichiometric composition of the target compound, and the same production method as in Example 1 was carried out to obtain a Li 3.6 Ge 0.6 V 0.4 An oxide-based solid electrolyte with a composition of O4.
[0087] (Example 6)
[0088] In a glove box with an argon atmosphere, the raw materials were weighed so that the raw material charge composition became the stoichiometric composition of the target compound, and the same production method as in Example 1 was carried out to obtain a Li 3.7 Ge 0.7 V 0.3 An oxide-based solid electrolyte with a composition of O4.
[0089] (Example 7)
[0090] In a glove box with an argon atmosphere, the raw materials were weighed so that the raw material charge composition became the stoichiometric composition of the target compound, and the same production method as in Example 1 was carried out to obtain a Li 3.3 Ge 0.3 V 0.7 An oxide-based solid electrolyte with a composition of O4.
[0091] (Example 8)
[0092] In a glove box with an argon atmosphere, the raw materials were weighed so that the raw material charge composition became the stoichiometric composition of the target compound, and the same production method as in Example 1 was carried out to obtain a Li 3.75 Ge 0.75 P 0.25 An oxide-based solid electrolyte with a composition of O4.
[0093] (Example 9)
[0094] In a glove box with an argon atmosphere, the raw materials were weighed so that the raw material charge composition became the stoichiometric composition of the target compound, and the same production method as in Example 1 was carried out to obtain a Li 3.5 Ti 0.5 V 0.5 An oxide-based solid electrolyte with a composition of O4.
[0095] (Comparative Example 1)
[0096] Prepare to have Li 6.25 Al 0.25 La3Zr2O 12 An oxide-based solid electrolyte with a composition of
[0097] (Comparative Example 2)
[0098] Prepare to have Li 0.33 La 0.56 An oxide-based solid electrolyte with a composition of TiO3.
[0099] (Comparative Example 3)
[0100] Prepare to have Li 1.3 Al 0.3 Ti 1.7 An oxide-based solid electrolyte with a composition of (PO4)3.
[0101] <2. Preparation of positive electrode active material>
[0102] (Example 1)
[0103] Prepare LiNi 0.6 Co 0.2 Mn 0.2 Positive electrode active material composed of O2.
[0104] (Examples 2, 3, 5 to 9, Comparative Examples 1 to 3)
[0105] Prepare LiNi 0.82 Co 0.15 Mn 0.03 Positive electrode active material composed of O2.
[0106] (Example 4)
[0107] Prepare LiNi 0.9 Co 0.07 Mn 0.03 Positive electrode active material composed of O2.
[0108] The composition evaluation of the positive electrode active material prepared in Examples 1 to 9 and Comparative Examples 1 to 3 was performed as described below. That is, 5 g of a sample (powder) of each positive electrode active material was weighed, decomposed by an alkali fusion method, and then the composition analysis was performed using an inductively coupled plasma emission spectrometer (ICP-OES) "PS7800" manufactured by Hitachi High-Technologies Co., Ltd. The oxygen content was obtained by subtracting the analysis values of Li and metal components from the total amount of the analyzed sample, and also subtracting the impurity concentration and the residual alkali amount, and the z value of the oxygen composition (Oz) was calculated based on the oxygen content.
[0109] <3. Evaluation of the reactivity between the positive electrode active material and the solid electrolyte (XRD evaluation)>
[0110] (Examples 1 to 9, Comparative Examples 1 to 3)
[0111] The obtained positive electrode active material and oxide-based solid electrolyte were weighed in a mass ratio of 1:1, and gently mixed manually with a pestle and mortar to obtain a positive electrode material / solid electrolyte mixed powder. The obtained mixed powder was pressed at 333 MPa to form a mixed powder compact. Next, the obtained compact was placed in an alumina boat covered with gold foil, and after sintering at 800°C for 2 hours, the obtained sintered body was crushed with a pestle and mortar. The mixed sintered powder obtained in this way was subjected to the following reactivity evaluation (XRD evaluation).
[0112] That is, the reactivity of the positive electrode active material and the solid electrolyte of Examples 1 to 9 and Comparative Examples 1 to 3 was analyzed by powder X-ray diffraction method: XRD (θ / 2θ method) according to the following conditions. When the X-ray diffraction pattern obtained from the positive electrode material / solid electrolyte mixed powder is different before and after sintering, it means that a new peak is generated after sintering and the peak existing before sintering disappears, so the reaction product of the positive electrode active material and the oxide-based solid electrolyte (NCM) is evaluated as "present". On the other hand, when the obtained X-ray diffraction patterns are the same, the reaction product of the positive electrode active material and the oxide-based solid electrolyte (NCM) is evaluated as "absent".
[0113] ·X-ray diffraction apparatus: SmartLab manufactured by Rigaku Corporation.
[0114] ·Light source: CuKα rays.
[0115] Voltage: 40kV.
[0116] Current: 30mA.
[0117] The obtained X-ray diffraction patterns of Examples 1 to 9 and Comparative Examples 1 to 3 are shown in FIG. Figures 2 to 13 .exist Figures 2 to 13 In the figure, the X-ray diffraction patterns are recorded in a vertical alignment, wherein the lower X-ray diffraction pattern represents the pattern before firing, and the upper X-ray diffraction pattern represents the pattern after firing. Figures 2 to 10 In (Examples 1 to 9), it is found that the upper and lower X-ray diffraction patterns (X-ray diffraction patterns before and after sintering) are the same. Figures 11 to 13 In (Comparative Examples 1 to 3), it was found that the upper and lower X-ray diffraction patterns (X-ray diffraction patterns before and after firing) were different, and new peaks were generated after firing or peaks existing before firing disappeared.
[0118] <4. Fabrication of all-solid-state lithium-ion batteries>
[0119] (Examples 1 to 9, Comparative Examples 1 to 3)
[0120] The obtained positive electrode active material, oxide-based solid electrolyte and binder are mixed in a mass ratio of 50:50:5 in sequence, anisole is added as a solvent so that the solid content of the slurry becomes about 55 mass%, and mixed with MAZERUSTAR for 400 seconds to prepare a positive electrode composite material slurry. After the solvent of the obtained slurry is dried at room temperature, it is crushed with a pestle and mortar to obtain a positive electrode composite material powder.
[0121] In Example 3, gold powder was added as a conductive auxiliary agent to the constituent raw materials of the positive electrode composite material slurry in an amount twice the mass of the positive electrode material.
[0122] Next, about 10 mg of the positive electrode composite material powder was placed on the pre-pressed oxide-based solid electrolyte, and pressed at 333 MPa to produce a solid electrolyte layer / positive electrode composite material layer laminate.
[0123] Next, the above-mentioned stacked body is placed on a MgO or ZrO2 refractory setter and sintered at 800°C for 2 hours to produce a sintered body of the solid electrolyte layer / positive electrode composite material layer.
[0124] Next, the polymer solid electrolyte and metal Li were crimped on the negative electrode side of the solid electrolyte layer to form a negative electrode layer. The laminated body thus prepared was placed in a sealed SUS304 battery test cell to isolate the atmosphere, and a restraining pressure of 0.4 N·m was applied to prepare an all-solid-state secondary battery. In this way, an all-solid-state lithium-ion battery was prepared.
[0125] <5. Evaluation of composition of oxide-based solid electrolyte>
[0126] 0.5 g of samples (powder) of each oxide-based solid electrolyte obtained in Examples 1 to 9 and Comparative Examples 1 to 3 were weighed, dissolved using various acids, and then analyzed for composition using an inductively coupled plasma optical emission spectrometer (ICP-OES) "PS7800" manufactured by Hitachi High-Technologies Corporation.
[0127] <6. Charge and discharge test>
[0128] The all-solid lithium ion batteries of Examples 1 to 9 and Comparative Examples 1 to 3 were each subjected to initial charge and discharge at 60° C. and 0.05 C to evaluate initial charge and discharge capacities. In Comparative Examples 1 to 3, since no capacity was obtained, the values were set as N / D.
[0129] Table 1 shows the above-mentioned production conditions and test results.
[0130] [Table 1]
[0131]
[0132] (Evaluation results)
[0133] For Examples 1 to 9, the X-ray diffraction pattern of the powder compact obtained by mixing and pressing the oxide-based solid electrolyte and the positive electrode active material was compared with the X-ray diffraction pattern of the sintered body obtained by sintering the powder compact. As a result, the X-ray diffraction patterns of each other were the same, so it was judged that the reactant of the oxide-based solid electrolyte and the positive electrode active material was not generated. Moreover, in the case where the reactant was not generated, it can be evaluated that the battery characteristics of the all-solid-state battery are good, and the charge and discharge capacity of the all-solid-state battery was actually measured, and the result was a good result.
[0134] For Comparative Examples 1 to 3, the X-ray diffraction pattern of the powder compact obtained by mixing and pressing the oxide-based solid electrolyte and the positive electrode active material was compared with the X-ray diffraction pattern of the sintered body obtained by sintering the powder compact. As a result, the X-ray diffraction patterns of each other were different, so it was judged that a reactant of the oxide-based solid electrolyte and the positive electrode active material was generated. In addition, when the reactant was generated, it can be evaluated that the battery characteristics of the all-solid-state battery are poor. The charge and discharge capacity of the all-solid-state battery was actually measured, and as a result, no capacity was obtained.
[0135] As can be seen from the above, according to the evaluation method of the all-solid-state lithium-ion battery of the present invention, the battery characteristics of the oxide-based all-solid-state battery can be efficiently evaluated.
Claims
1. A method for evaluating an all-solid-state lithium-ion battery, wherein: The all-solid-state lithium-ion battery comprises: a solid electrolyte layer including an oxide-based solid electrolyte, a positive electrode layer including a positive electrode active material, and a negative electrode layer. In the evaluation method of the all-solid-state lithium-ion battery, The battery characteristics of the all-solid-state lithium-ion battery are evaluated by comparing an X-ray diffraction pattern of a powder compact obtained by mixing and pressing the oxide-based solid electrolyte and the positive electrode active material and an X-ray diffraction pattern of a sintered body obtained by sintering the powder compact.
2. The evaluation method of an all-solid-state lithium-ion battery according to claim 1, wherein: The X-ray diffraction pattern of a powder compact obtained by mixing and pressing the oxide-based solid electrolyte and the positive electrode active material is compared with the X-ray diffraction pattern of a sintered body obtained by sintering the powder compact. When the X-ray diffraction patterns are different, it is judged that a reactant between the oxide-based solid electrolyte and the positive electrode active material is generated. When the X-ray diffraction patterns are the same, it is judged that a reactant between the oxide-based solid electrolyte and the positive electrode active material is not generated, thereby evaluating the battery characteristics of the all-solid-state lithium-ion battery.
3. The method for evaluating an all-solid-state lithium-ion battery according to claim 1 or 2, wherein: The oxide-based solid electrolyte has a composition formula 1: Li α A x M y O4 represents that in the composition formula 1, A is Ge, Si or Ti, M is V, P or As, 3.25≤α≤3.75, 0.30≤x≤0.75, and 0.25≤y≤0.70, The positive electrode active material has a composition formula 2: Li a Ni b Co c Mn d O2 represents that in composition formula 2, 1.00≤a≤1.08, 0.60≤b≤0.90, and b+c+d=1.0.